Cloud fraction response to aerosol driven by nighttime processes - Geoffrey Pugsley; Edward Gryspeerdt; Vishnu Nair (Proceedings of the National Academy of Sciences, 2025)
Aerosol–cloud interactions remain one of the largest uncertainties in the anthropogenic forcing of the climate; a significant contribution to this is due to the aerosol effect on the development of cloud fraction and liquid water path in stratocumulus clouds. Stratocumulus are strongly modulated by the diurnal cycle, but many previous observational studies have primarily focused on the daytime behavior of these clouds. In this work, a Lagrangian framework is used to characterize the day-night variation in the cloud sensitivity to aerosol. It is shown that the cloud fraction response to aerosol is driven by nighttime processes, whereas aerosols play a lesser role in daytime cloud fraction breakup. The liquid water path response reveals that aerosols act to thin the cloud during the daytime; however, this effect is partially offset by other processes during the nighttime. These nighttime cloud processes play an important role in setting the cloud state at the start of the day and hence the daytime cloud evolution, during which stratocumulus clouds have the greatest radiative impact. Our findings are consistent with an aerosol induced suppression of precipitation that acts most effectively at night, when stratocumulus precipitation is strongest. These results highlight a requirement for nighttime observations of marine clouds and an improved representation of the diurnal cycle in model-observation comparisons, especially when assessing climate forcing and the viability of marine cloud brightening.